2015
DOI: 10.1155/2015/686571
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of Secretory Cells of the Islets of Langerhans in South American Catfish Rhamdia quelen

Abstract: The present work shows that a detailed description of the ultrastructure of the secretory cells of the South American catfish Rhamdia quelen pancreatic islets is presented. Evidence is offered to support the contention that the -granules consist of a central and an outer portion of different electron densities and solubilities, that the -cells are most probably morphologically altered but viable -cells, and that the -granules possibly possess a repeating substructure and may therefore represent an intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Similar findings were reported in the compact pancreas (Sheibani & Pahlavan Yali, 2006; Naguib et al., 2009; Mokhtar, 2015). The endocrine portion appeared as pale staining islets distributed among the exocrine tissue, similar to that recorded in other previous reports (Chakrabarti & Ghosh, 2015; Luchini et al., 2015). Endocrine tissue consisted of large principal islet and numerous smaller islets, as in most previous studies (Stefan & Falkmer, 1980; Groff & Youson, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were reported in the compact pancreas (Sheibani & Pahlavan Yali, 2006; Naguib et al., 2009; Mokhtar, 2015). The endocrine portion appeared as pale staining islets distributed among the exocrine tissue, similar to that recorded in other previous reports (Chakrabarti & Ghosh, 2015; Luchini et al., 2015). Endocrine tissue consisted of large principal islet and numerous smaller islets, as in most previous studies (Stefan & Falkmer, 1980; Groff & Youson, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…In fish, it has been reported that the alimentary pattern could affect hormonal secretion (Navarro et al., 2002). Furthermore, two forms of the pancreas (compact and disseminated) were reported in various fish species (Chen et al., 2006; Youson et al., 2006; Tocher et al., 2008; Luchini et al., 2015; Mokhtar, 2015); however, reports explaining the localization and morphology of disseminated portion in catfish remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal ganglion was taken as the largest cranial nerve extending rostrally from underneath the hindbrain. Pancreatic tissue was taken as the fatty tissue that connects the triangular shape made by the liver, stomach, and spleen as described in Luchini et al (2015) . Animals were captured, held, and euthanized under permit (33/2017) from the Foreign and Colonial Office of the United Kingdom under the Antarctic Act 1994/Antarctic Act 2013, Antarctic Regulations 1995/490 (as amended).…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth noting that the B granules containing the crystalline‐like core in the embryonic pancreas of the grass snake are similar to the B granules that have been described in the pancreas of most vertebrate species (Bencosme & Pease, ; Pictet & Rutter, ; Hotta, Mabuchi, & Watari, ; Slack, ). Such granules have been described in the adult pancreas of catfish (Luchini, Wicki, & Romano, ), cat (Bencosme & Pease, ; Legg, ), dog (Hotta et al, ), and rat (Greider, Howell, & Lacy, ; Michael, Carroll, Swift, & Steiner, ), as well as in the pancreas of vertebrate embryos (Pictet & Rutter, ; Miralles et al, ). Therefore, what causes the pancreatic B granules in most vertebrate species to have a crystalline core?…”
Section: Discussionmentioning
confidence: 97%